Immunotoxic effects of exposure to the antifouling copper(I) biocide on target and nontarget bivalve species: a comparative in vitro study between Mytilus galloprovincialis and Ruditapes philippinarum - Cima, Francesca; Varello, Roberta (Frontiers in Physiology, 2023)
Edible bivalves constitute an important bioresource from an economic point of view, and studies on their immune responses to environmental pollutants are crucial for both the preservation of biodiversity and economic reasons. The worldwide diffusion of copper(I)-based antifouling paints has increased copper leaching into coastal environments and its potential impact on both target and nontarget organisms. In this study, immunotoxicity assays were carried out with short-term (60 min) cultures of hemocytes from the bivalves Mytilus galloprovincialis -a mussel dominant in the macrofouling community -and Ruditapes philippinarum -a clam dominant in the soft-sediment community -exposed to CuCl to compare the toxic effects on their immune responses. The LC 50 values were similar, 40 μM (3.94 mg L -1 ) for the mussel and 44 μM (4.33 mg L -1 ) for the clam. In both species, apoptosis occurred after exposure to 1 µM (98.9 µg L -1 ) CuCl, the concentration able to significantly increase the intracellular Ca 2+ content. Biomarkers of cell morphology and motility revealed microfilament disruption, a significant decrease in yeast phagocytosis and lysosome hydrolase (β-glucuronidase) inhibition beginning from 0.5 µM (49.5 µg L -1 ) CuCl in both the mussel and clam. The same concentration of CuCl affected biomarkers of oxidative stress, as a significant decrease in reduced glutathione content in the cytoplasm and inhibition of mitochondrial cytochrome-c oxidase (COX) were detected in both species. Comparison of the biomarkers showed that clam is more sensitive than the mussel regarding alterations to the lysosomal membrane and ROS production, which supports the potential harmful effects of antifouling biocides on the survival of nontarget pivotal species in the coastal community.